Enzyme catalysis at high hydrostatic pressure - Schmalle, Marlene (2024)
In the past, several methods have been developed to improve the application of the biocatalysts, such as immobilizing enzymes on support materials to ensure reusability, improve stability, and maintain their activity. Furthermore, the use of non-aqueous media and genetic engineering has been applied to further enhance the enzyme performance with respect to stability, activity and selectivity. However, the evaluation of additional or synergistic process parameters is still part of research with the aim of enabling the application of enzymes in chemical synthesis. Recently, the application and effect of high hydrostatic pressure (HHP) to enzymatic catalyzed reactions is becoming increasingly important. This thesis explored the synergistic potential of combining common and innovative methods to improve enzyme performance with superior stabilization and enzyme activity, thereby contributing to the development of more efficient biocatalysts. In order to investigate the effect of HHP on three different enzymes, a reactor concept was designed first. A continuously operated packed bed reactor (PBR) was selected to fulfill the requirement for continuous operation as part of process intensification and to enable quick and easy adjustment of process parameters. An appropriate immobilization method was developed for two selected lipases to ensure their application in a packed bed reactor (PBR) with the highest loading of the enzyme immobilizates possible. In particular, mechanical stability during continuous reactor operation under ambient and high hydrostatic pressure conditions and the leaching of enzymes from the carrier were investigated. After the establishment of the HHP reactor system, the influence of HHP on the enzyme performance including enzyme stability, activity, selectivity and kinetic parameters was investigated representing the core of the thesis. Three industrially relevant enzymes, Candida rugosa lipase (CRL) and Candida antarctica lipase B (CalB) from enzyme class 3 (EC 3), as well as Ruegeria pomeroyi ...